Selection-based learning in bird song development. - Nelson, D A (1994)
Bird song is a model system for study of the neurobiology, development, and functions of learned vocal communication signals. Research on avian song learning has been dominated by an instructive model of learning--the sensorimotor model. Developmental plasticity is assumed to be based on the incorporation of novel material into the song repertoire. Experimental evidence now indicates an alternative form of plasticity operating in harmony with sensorimotor learning, based on principles of selection, rather than instruction. Song dialects, a common consequence of vocal learning, can be achieved by overproduction of previously memorized songs and selective attrition of those that fail to match the dialect of interacting males. These distinct processes of learning have important implications for study of the neural substrates underlying song production and perception and for efforts to interpret patterns of geographic variation in song.